2020
DOI: 10.1007/s40279-020-01363-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Reducing the Impact of Cycling on the Perineum in Healthy Males: Systematic Review and Meta-analysis

Abstract: Introduction Perineal pressure associated with bicycle riding is the cause of several genitourinary pathologies, most notably Alcock’s syndrome and subsequent perineal numbness. The possible link between cycling-induced perineal numbness and erectile dysfunction makes the development of strategies for perineal protection in bicycle users critical. Objective To assess the effectiveness of strategies for reducing the impact of cycling on the perineum in healthy males. Methods We have conducted a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Cycling has been recognized as an important means of promoting public health and it is among the most popular sports [1][2][3]. However, the constant pressure exerted on the bicycle seat might be the cause of non-traumatic injuries [4], ranging from saddle sores to more serious disorders related to the urogenital system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cycling has been recognized as an important means of promoting public health and it is among the most popular sports [1][2][3]. However, the constant pressure exerted on the bicycle seat might be the cause of non-traumatic injuries [4], ranging from saddle sores to more serious disorders related to the urogenital system [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the study by Sommer et al (2001) [10] confirmed that pedaling in an upright position does not cause any alteration of the penile blood supply. As a matter of fact, the constant pressure exerted on the bicycle saddle could be the cause of non-traumatic injuries [11], ranging from saddle sores to more serious disorders related to the urogenital system [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the measurement of pressures in the saddle and the related compression on the perineum has been investigated [ 14 ]. A survey of 2,774 cyclists and 1,158 non-cyclists revealed that cycling is associated with a significantly higher risk of perineal numbness and urethral stricture development [ 12 ]. Up to 91% of cyclists experienced perineal numbness.…”
Section: Introductionmentioning
confidence: 99%